Design and Implementation of an Internet of Things-Based Automatic Plant Watering System for Household Environments with Mobile Control - Adi Wahyu Candra Kusuma; Azka Rijaalunnaafian; Novian Affan; Putra Aditya; Anggin Mayastari; Azora Sania Salma; Hasna Nur Askhia (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The development of Internet of Things (IoT) technology enables physical devices to operate intelligently through remote monitoring and control processes. One of its applications is an automatic plant watering system designed to assist in plant care without the need for manual watering at all times. This system is intended for users who enjoy gardening or maintaining plants but have limited time to water them regularly. This project develops a watering system based on ESP32, connected to a soil moisture sensor to monitor the condition of the growing media in real time. When the moisture level falls below a certain threshold, a water pump is automatically activated according to a predefined watering duration. The system integrates hardware components, namely the ESP32 and sensors, with the Firebase cloud service. In addition, users can manually control the system through a Wi-Fi-based mobile application. The project demonstrates that the system operates effectively. This solution has the potential for further development, such as optimizing the watering algorithm, integrating data storage, and improving water usage efficiency through long-term moisture pattern analysis.